From dusk to dawn: local party organization and party success of right-wing extremism - Dinas, E; Georgiadou, V; Konstantinidis, I; Rori, L (SAGE Publications, 2016)
A marginal racist organization, Golden Dawn, managed to attract first the votes of almost one out of 14 Greek voters and then global media and public attention. How did an extreme right groupuscule invade the political terrain of an EU-10 member state? Existing attempts to account for this phenomenon point to demand-side explanations, related to the political turmoil that followed the notorious debt crisis and the accompanying austerity measures. These explanations, however, fail to account for the genesis of this trajectory. We delve into this exact question, focusing on the election that marked the emergence of the Golden Dawn and permitted further electoral penetration. Combining qualitative and quantitative methods, we show that the party took advantage of favourable political circumstances developing a grassroots network of protection that helped it enter the central political arena.